A frictional sliding on a sprung slope (FSSS) device that axiomatically confers energy dissipation with re-centring to post-tensioned (PT) frames: A conceptual study. (1st October 2021) - Zhang, Yichen; De Risi, Raffaele; Alexander, Nicholas Andrew
Highlights: A novel dissipative device with zero-sliding activation force threshold and amplitude-dependent resistive force is presented. The device guarantees re-centring for the post-tensioned (PT) frames equipped with it. The device is demonstrated to be effective in reducing seismic responses of PT frames. The equivalent damping ratio of the PT frames equipped with the proposed device increases with drift amplitude. Abstract: A conceptual novel frictional sliding on a sprung slope (FSSS) device is proposed for application with post-tensioned (PT) frames (which have a nonlinear elastic characteristic). This FSSS device has an amplitude-dependent hysteretic resistance nature. The mechanical schematization and design implementation are presented, followed by its analytical formulations. Theoretical analysis indicates that the estimated equivalent viscous damping ratio of the PT frame with the FSSS device must increase with the amplitude of drift ratio oscillations. Three heuristic PT frames with and without the FSSS device are analysed numerically using OpenSees as a numerical proof-of-concept. Both quasi-static (cyclic push-over) and nonlinear dynamic structural analyses are performed. The numerical results of the PT part are benchmarked against the experimental test, and those of the FSSS part are verified by the theoretical formulations. Quasi-static cyclic tests indicate that the PT frame with the FSSS device has a triangular flag-shaped hysteretic curve rather than a parallelogram flag-shape, as in traditional self-centring systems. This triangular flag-shape is an advantage as it does not inhibit re-centring of the PT frame as its activation force threshold is effectively zero. Incremental dynamic analyses (IDA) are also carried out for a set of ground motions. The IDA results show that the device significantly reduces the earthquake response of the PT frame in terms of drift ratios. Additionally, no residual deformations are observed after the earthquake excitations, validating the axiomatic self-centring feature of the PT frames with FSSS devices.